A return to the ground: movement, land, and modes of existence in Nkambeni, South Africa - Visser, Jacobus (ANS: Anthropology, 2026)
This dissertation explores the role of land in Nkambeni, a rural chieftaincy in northeastern South Africa with a history of colonial and apartheid displacement and enclosures, to engage the question of being – approached here, following Bruno Latour, as modes of existence. Based on two months of ethnographic fieldwork, with farming and gardening as entry points, the dissertation argues that land reveals movement – conceptual, spatial, and relational – as central to the shaping of reality in Nkambeni. These movements are traced through the flows of knowledge, soil, and water, foregrounding tensions between modernist and otherwise ways of being. Such entanglements point to a compositeness, building on Francis Nyamnjoh's articulation of the concept, where existence does not emerge through commensurability but through continuous movements across difference. In response, the study proposes a methodological framework grounded in movement itself – not only as an analytic but as a moral and ethical orientation, where participation demands a form of ‘becoming with' that entails an obligatory, often messy, and even violent reciprocity. Anna Tsing's ‘multispecies attunement' is central to this approach, evoking a sensitivity to human and more-than-human entanglements through that which lay just beyond perceptibility in this ever-shifting landscape. It unsettles hegemonic framings of space and place as fixed, knowable, or enclosed, offering instead a methodology that remains accountable to the frictions and uncertainties of the field. To this end, the dissertation rethinks land not as a passive backdrop but as an active participant in shaping being, revealing the limits of modernist dualisms that separate subject from object, human from non-human, substance from medium, real from symbolic, fixed from fluid. Here, two modes of existence emerged as central to this analysis: indebtedness and metamorphoses. The mode of indebtedness, revealed through the soil, animated ongoing movement across the compositeness of give and take, life and death, pointing to an entangled form of sustenance that unfolded in a polyphony of times. The mode of metamorphoses, revealed through, with, and as water, pointed to how power shifted and enabled transformation, transfiguration, and transubstantiation beyond fixed hierarchical binaries. These modes demonstrate – however partially sensed – how existence in Nkambeni, through movement, was shaped in ways that exceeded what modernist articulations of the world can encapsulate, even as it remained fixed within it. Thus, the study critically reflects on the ontological categories of space and place, time, and ideas of power embedded in fixed binary hierarchies. Here, the title, A Return to Ground, becomes a discursive and recursive motif that continuously questions the starting point from which to theorise being in a world, or worlds, where aspects of reality persistently remain just beyond reach. Ultimately, the research contributes to emerging decolonial scholarship in the humanities by offering a recursive account of movement and compositeness as both method and encounter, enabling an exploration of ontological questions in postcolonial Africa. This study is not a mere rejection of modernity; it attends to its enduring effects while tracing how existence in Nkambeni exceeds its binary logics through composite, more-than-human engagements with land. Following land's generativity – through practice, weeds, soil, and water – it rethinks how difference and sameness are lived in composition. This intervenes in broader discourses on decolonial thought, the ontological turn, pluriversality, and ethics, by pushing the boundaries from which ontological and epistemological claims can be reimagined – not as fixed, but as moving and entangled in compositeness.j